2017
DOI: 10.1126/science.aal3485
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Gli2 activity coordinates a niche signaling program for mammary epithelial stem cells

Abstract: The stem cell niche is a complex local signaling microenvironment that sustains stem cell activity during organ maintenance and regeneration. The mammary gland niche must support its associated stem cells while also responding to systemic hormonal regulation that triggers pubertal changes. We find that , the major Hedgehog pathway transcriptional effector, acts within mouse mammary stromal cells to direct a hormone-responsive niche signaling program by activating expression of factors that regulate epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
(67 reference statements)
2
46
1
Order By: Relevance
“…Recent work, however, has shown that in the pubertal and adult mammary gland Hedgehog activity mediated by the transcriptional effector Gli2 is required to specify a stromal cell niche signaling program involving expression of both paracrine factors and hormone receptors. The Gli2-specified niche supports mammary epithelial stem cells in pubertal and virgin adult mice (Zhao et al, 2017). In the mammary gland, Gli2 expression is initially induced by crosstalk with TGFβ1 produced by adjacent epithelial cells.…”
Section: Specification Of the Stromal Niche In Bladder And Mammary Glandmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work, however, has shown that in the pubertal and adult mammary gland Hedgehog activity mediated by the transcriptional effector Gli2 is required to specify a stromal cell niche signaling program involving expression of both paracrine factors and hormone receptors. The Gli2-specified niche supports mammary epithelial stem cells in pubertal and virgin adult mice (Zhao et al, 2017). In the mammary gland, Gli2 expression is initially induced by crosstalk with TGFβ1 produced by adjacent epithelial cells.…”
Section: Specification Of the Stromal Niche In Bladder And Mammary Glandmentioning
confidence: 99%
“…The mammary ductal defects in Gli2 ΔS mice thus are not rescued by growth hormone, but are rescued by local supplementation with the stromally-expressed paracrine factors induced by growth hormone (Igf1 and Wnt2b) (Zhao et al, 2017). This type of niche failure may explain the pathogenesis of certain human diseases sometimes associated with GLI2 mutation, including the deficient breast development and hormonal insensitivity associated with the human disorder combined pituitary hormone deficiency, (Darendeliler et al, 2011; Maghnie et al, 2006).…”
Section: Specification Of the Stromal Niche In Bladder And Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the tissue compartment specific roles of Gli2 have been further defined using Fsp-Cre;Gli2 conditional ablation animals [69]. This animal displays reduced proliferation, reduced stroma adjacent to mammary epithelium, hypoplasia, and reduced collagen deposition [69].…”
Section: Hedgehog Signaling Network In Mammary Gland Developmentmentioning
confidence: 99%
“…Differences in the biological activities of GLI1 and GLI2 are evident, since GLI1 knockout mice have no obvious phenotype [46], in contrast to GLI2 knockout mice which die at birth [47, 48]. Gli2 is important for several physiological functions [49], and possibly is expressed in a different subset of bone marrow cells than Gli1. Consequently, blocking Gli2 may cause several undesired side effects in the patients with myelofibrosis.…”
Section: Clinical Intervention For Myelofibrosismentioning
confidence: 99%